Atrioventricular shortening is the dominant mechanism of benefit of biventricular pacing in left bundle branch block. (24th May 2021) - Arnold, A; Shun-Shin, MJ; Ali, N; Howard, JP; Keene, D; Chow, J; Qureshi, N; Lefroy, DC; Koa-Wing, M; Linton, NWF; Lim, PB; Peters, NS; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): British Heart Foundation Background: Cardiac resynchronization therapy delivered via biventricular pacing is thought to improve haemodynamic function through resynchronization of ventricular activation. Biventricular pacing also improves ventricular filling by shortening atrioventricular delay. Quantifying the relative contributions of these two mechanisms requires atrioventricular delay to be altered while left bundle branch block is preserved. This occurs when the His bundle is paced at an output below the left bundle branch block correction threshold. Purpose We performed His bundle pacing with preservation of left bundle branch block to measure the relative contributions of atrioventricular delay shortening and ventricular resynchronisation to the overall haemodynamic benefit of biventricular pacing. Methods: Patients with left bundle branch block referred for conventional cardiac resynchronization therapy with biventricular pacing were recruited. Using a high precision, beat-by-beat systolic blood pressure assessment protocol, we assessed the haemodynamic effects of biventricular pacing and temporary His bundle pacing with left bundle branch block preservation at a full range of atrioventricular delays. We used non-invasive epicardial mapping (ECGI) to assess left ventricular activation time. Left bundle branch block preservation was defined as <20ms shortening of the interval between intrinsic His potential to QRS offset to the interval from stimulation to QRS offset in His bundle pacing. Results: In 19 patients, His bundle pacing with preservation of left bundle branch block produced a peak systolic blood pressure improvement of 5.1mmHg (95% confidence interval: 2.2 to 8.0, p = 0.0013) compared to AAI pacing. In 16 of these patients, biventricular pacing was performed and produced a peak systolic blood pressure improvement of 7.1mmHg (3.8 to 10.4, p < 0.001) compared to AAI pacing. The mean within-patient improvement in systolic blood pressure from His bundle pacing with preservation of left bundle branch block to biventricular pacing was 2.6mmHg (-0.4 to 5.7, p = 0.053, n = 16). The mean improvement in systolic blood pressure with left bundle branch block-preserved His bundle pacing was 63% of the mean improvement with biventricular pacing. Change in left ventricular activation time from intrinsic rhythm to 12-lead-ECG-defined left bundle branch block preservation was 0.1ms (-6.4 to 6.7, n = 19). Conclusion: Biventricular pacing in left bundle branch block improves haemodynamic function through ventricular resynchronization and shortening of atrioventricular delay. The majority of benefit appears to be produced by atrioventricular delay shortening. When left bundle branch block is not corrected, His bundle pacing may still produce considerable haemodynamic improvement through this mechanism.